Asn(347) Glycosylation of Corticosteroid-binding Globulin Fine-tunes the Host Immune Response by Modulating Proteolysis by Pseudomonas aeruginosa and Neutrophil Elastase - Sumer-Bayraktar, Zeynep (J Biol Chem, 2016)
Corticosteroid-binding globulin (CBG) delivers anti-inflammatory cortisol to inflamed tissues upon elastase-based proteolysis of the exposed reactive center loop (RCL). However, the molecular mechanisms that regulate the RCL proteolysis by co-existing host and bacterial elastases in inflamed/infected tissues remain unknown. We document that RCL-localized Asn(347) glycosylation fine-tunes the RCL cleavage rate by human neutrophil elastase (NE) and Pseudomonas aeruginosa elastase (PAE) by different mechanisms. NE- and PAE-generated fragments of native and exoglycosidase-treated blood-derived CBG of healthy individuals were monitored by gel electrophoresis and LC-MS/MS to determine the cleavage site(s) and Asn(347) glycosylation as a function of digestion time. The site-specific (Val(344)-Thr(345)) and rapid (seconds to minutes) NE-based RCL proteolysis was significantly antagonized by several volume-enhancing Asn(347) glycan features (i.e. occupancy, triantennary GlcNAc branching, and α1,6-fucosylation) and augmented by Asn(347) NeuAc-type sialylation (all p < 0.05). In contrast, the inefficient (minutes to hours) PAE-based RCL cleavage, which occurred equally well at Thr(345)-Leu(346) and Asn(347)-Leu(348), was abolished by the presence of Asn(347) glycosylation but was enhanced by sialoglycans on neighboring CBG N-sites. Molecular dynamics simulations of various Asn(347) glycoforms of uncleaved CBG indicated that multiple Asn(347) glycan features are modulating the RCL digestion efficiencies by NE/PAE. Finally, high concentrations of cortisol showed weak bacteriostatic effects toward virulent P. aeruginosa, which may explain the low RCL potency of the abundantly secreted PAE during host infection. In conclusion, site-specific CBG N-glycosylation regulates the bioavailability of cortisol in inflamed environments by fine-tuning the RCL proteolysis by endogenous and exogenous elastases. This study offers new molecular insight into host- and pathogen-based manipulation of the human immune system.